1987
DOI: 10.1111/j.1365-2591.1987.tb00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the canal space occupied by gutta‐percha following lateral condensation and thermomechanical condensation

Abstract: Summary. Since root canal sealers and pastes can cause tissue irritation, the quantity of biologically inert gutta‐percha should constitute more than 90 per cent by volume of the root canal filling. The root canals of 40 extracted incisors with straight root canals were enlarged sequentially to size 50 and the canals were obturated, either by lateral condensation or thermomechanical condensation using standardized gutta‐percha points and Grossman's sealer. After being stored in moistened gauze for 6 hours at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
2
0
5
Order By: Relevance
“…8,[12][13][14] In general, the higher the PGP, the smaller the area of sealer and voids, the better the quality of the root canal filling. 4,15 The PGP score may reveal filling problems in the oval canal.…”
Section: Introductionmentioning
confidence: 98%
“…8,[12][13][14] In general, the higher the PGP, the smaller the area of sealer and voids, the better the quality of the root canal filling. 4,15 The PGP score may reveal filling problems in the oval canal.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies, comparing the effectiveness of filling techniques, have given conflicting results. Some (Peters 1986, Beer et al 1987, Jacobsen & Begole 1992, Liewehr et al 1993 reported that none of the techniques studied provided a superior seal whilst other studies reported better filling of lateral canals (Brothman 1981, Clark & ElDeeb 1993, Goldberg et al 2001 and better outcomes from treatments using warm gutta-percha (Farzaneh et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos têm evidenciado sua capacidade de proporcionar bom vedamento marginal, especialmente no terço apical [6][7][8] . Entretanto, Cohen e Burns 9 relatam que essa técnica não produz a fusão dos cones em uma massa única.…”
Section: Discussionunclassified